Scaling and institutionalization within agricultural innovation systems: the case of cocoa farmer field schools in Cameroon. Issue 2 (4th March 2018) - Muilerman, Sander; Wigboldus, Seerp; Leeuwis, Cees
ABSTRACT: The farmer field school (FFS) concept has been widely adopted, and such schools have the reputation of strengthening farmers' capacity to innovate. Although their impact has been studied widely, what is involved in their scaling and in their becoming an integral part of agricultural innovation systems has been studied much less. In the case of the Sustainable Tree Crops Programme in Cameroon, we investigate how a public–private partnership (PPP) did not lead to satisfactory widespread scaling in the cocoa innovation system. We build a detailed understanding of the key dimensions and dynamics involved and the wider lessons that might be learned regarding complex scaling processes in the context of agricultural innovation systems. Original interview data and document analysis inform the case study. A specific analytical approach was used to structure the broad-based exploration of the qualitative dataset. We conclude that scaling and institutionalization outcomes were impeded by: the lack of an adaptive approach to scaling the FFS curriculum, limited investments and genuine buy-in by extension actors, a failure to adapt the management approach between the pilot and the scaling phase, and the lack of strategic competencies to guide the process. Our findings support suggestions from recent literature that pilots need to be translated and adapted in light of specific contextual and institutional conditions, rather than approached as a linear rolling-out process. These findings are relevant for the further spread of similar approaches commonly involved in multi-stakeholder scaling processes such as innovation platforms. GRAPHICAL ABSTRACT: